Entomophily of Apple ecosystem in Kashmir valley, India: A review - Riyaz, Muzafar; Mathew, Pratheesh; Paulraj, Gabriel; Ignacimuthu, Savarimuthu (International Journal of Scientific Research in Biological Sciences, 2018)
Pollination is a prerequisite for the efficiency of the vast majority of the yields in agrarian and horticultural ecosystems. This is carried out mostly by insects which are the prime agents of pollination in flowering plants. The present article is a review of the pollination aspects of apple orchards of Kashmir. Apple inflorescence requires assistance from insects to carry out the process of pollination and hence more the number of pollinators, higher the chance for better crop yield. The most important role of pollination is played for the most part by the species of Hymenoptera in Apple ecosystems. The pollinators are declining steadily, because of habitat destruction and unrestrained use of agrochemicals, pesticides and other antifungal sprays. Necessary steps should be taken for a better understanding of diversity and bio-ecology of insects in agricultural fields such that the pests, pollinators and other beneficial insects could be monitored easily, which will further aid better and eco-friendly conservation and management tactics. Despite the fact that Kashmir is a leading apple producer in the country, productivity should be increased to meet future demand. New approaches are needed to increase apple production through sustainable ways including increasing insect pollinators that can be employed in apple orchards by farmers. Such a framework will enhance the economic growth from apple cultivation and furthermore conserve the natural pollinator species in Kashmir.